1993
DOI: 10.1088/0954-3899/19/7/013
|View full text |Cite
|
Sign up to set email alerts
|

Multistep compound reaction calculations using the Feshbach-Kerman-Koonin theory

Abstract: The cross sections of (n, n') and (n, p) reactions at 14 MeV on a range of nuclei ~IE analysed using the theory of Feshbach, Kennan and Koonin. The contributions of the multistep compound and multistep direct processes are evaluated, and the strength of the effective nucleorc nucleon potential delermined for both lhe zero-range and Yukawa potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Some progress has already been made towards this goal. Several early analyses of (n, n ) energy spectra in the backward direction for low incident energies, where MSC dominates, have shown that this process accounts well for the data for many nuclei with essentially the same parameters, including the effective nucleon-nucleon strength V 0 (Field et al 1986, Olaniyi et al 1993. Other analyses at higher incident energies similarly confirmed the validity of the MSD theory (Cowley et al 1991, Richter et al 1992 and showed that V 0 varies with incident energy.…”
Section: Introductionmentioning
confidence: 70%
“…Some progress has already been made towards this goal. Several early analyses of (n, n ) energy spectra in the backward direction for low incident energies, where MSC dominates, have shown that this process accounts well for the data for many nuclei with essentially the same parameters, including the effective nucleon-nucleon strength V 0 (Field et al 1986, Olaniyi et al 1993. Other analyses at higher incident energies similarly confirmed the validity of the MSD theory (Cowley et al 1991, Richter et al 1992 and showed that V 0 varies with incident energy.…”
Section: Introductionmentioning
confidence: 70%